Increased Risk for Malignancies in 131 Affected CTLA4 Mutation Carriers - Egg, David; Schwab, Charlotte; Gabrysch, Annemarie; Arkwright, Peter D.; Cheesman, Edmund; Giulino-Roth, Lisa; Neth, Olaf; Snapper, Scott; Okada, Satoshi; Moutschen, Michel; Delvenne, Philippe; Pecher, Ann-Christin; et al. (Frontiers in Immunology, 2018)
Background: Cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) is a negative immune regulator on the surface of T cells. In humans, heterozygous germline mutations in CTLA4 can cause an immune dysregulation syndrome. The phenotype comprises a broad spectrum of autoinflammatory, autoimmune, and immunodeficient features. An increased frequency of malignancies in primary immunodeficiencies is known, but their incidence in CTLA-4 insufficiency is unknown. Methods: Clinical manifestations and details of the clinical history were assessed in a worldwide cohort of 184 CTLA4 mutation carriers. Whenever a malignancy was reported, a malignancy-specific questionnaire was filled. Results: Among the 184 CTLA4 mutation carriers, 131 were considered affected, indicating a penetrance of 71.2%. We documented 17 malignancies, which amounts to a cancer prevalence of 12.9% in affected CTLA4 mutation carriers. There were ten lymphomas, five gastric cancers, one multiple myeloma, and one metastatic melanoma. Seven lymphomas and three gastric cancers were EBV-associated. Conclusion: Our findings demonstrate an elevated cancer risk for patients with CTLA-4 insufficiency. As more than half of the cancers were EBV-associated, the failure to control oncogenic viruses seems to be part of the CTLA-4-insufficient phenotype. Hence, lymphoproliferation and EBV viral load in blood should be carefully monitored, especially when immunosuppressing affected CTLA4 mutation carriers.